2012
DOI: 10.7860/jcdr/2012/4395.2629
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Nutritional Status of the Pre-School Children of the Employed Women and the Unemployed Women in the Urban Slums of Guntur

Abstract: Background: The early childhood development is most crucial and the mother's care and attention is essential. The inevitable changes like women entering the work field have an effect on the child care and development. Aim:To study the selected anthropometric indices of the children of employed and unemployed women. Settings and Design:This study was done in the urban slums of Guntur city by using a cross sectional, descriptive design. Methods and Material:This study was conducted during January -April 2011 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The lack of adult childcare support was linked to an increased risk of malnutrition in children from working and non-working mothers; however, the risk of malnutrition was higher in young children with working mothers. Yeleswarapu et al [ 26 ] investigated the nutritional status of young children with employed and unemployed mothers in urban slums in Andhra Pradesh, India. They found that weights and heights were significantly higher in children younger than five years of age from families with employed versus unemployed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of adult childcare support was linked to an increased risk of malnutrition in children from working and non-working mothers; however, the risk of malnutrition was higher in young children with working mothers. Yeleswarapu et al [ 26 ] investigated the nutritional status of young children with employed and unemployed mothers in urban slums in Andhra Pradesh, India. They found that weights and heights were significantly higher in children younger than five years of age from families with employed versus unemployed mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that birth weight, 31–33 maternal age, 31 parental smoking, 34,35 and financial status 33,36,37 are mainly associated with thinness in children. Factors associated with their body size included nutritional form, 38,39 daytime caregiver, 40,41 breakfast, 42,43 duration of sleep, 44 snacks, 43,44 and physical activity. 44,45…”
Section: Methodsmentioning
confidence: 99%
“…Most of the currently available studies 5,6,7,8 on working women's, focused most of their attention mainly on impact of their employment or economic independence on the health of working women's children, decline in duration of breast feeding, fertility trends and contraceptive use etc. Very few researchers studied the effect of economic dependence of the woman on her nutritional status itself.…”
Section: Introductionmentioning
confidence: 99%